A novel preparation method for monodisperse streptavidin magnetic beads and its application in electrochemiluminescent immunoassay for CEA - Hengbo Lei; Yuguo Tang (PLoS ONE, 2025)
The magnetic microspheres coated with streptavidin (PS-SA) were successfully prepared by loading streptavidin onto modified hyperbranched poly(glycerol) (HPG) magnetic microspheres. This material was comprehensively characterized using various methods, including scanning electron microscopy, thermogravimetric analysis, fourier-transform infrared spectroscopy, vibrating sample magnetometry and zeta potential measurement. This study introduced a novel electrochemiluminescence immunoassay utilizing functionalized magnetic microspheres for the ultrasensitive detection of carcinoembryonic antigen (CEA). The sensor employed Ru(bpy) 3 2+ -labeled anti-CEA-Ab2 (Ru-Ab2) as the signal probe and combined it with monodisperse streptavidin magnetic beads and biotinylated anti-CEA-Ab1 (bio-Ab1) to selectively capture CEA. Under optimized conditions, the immunosensor exhibited a broad linear range from 0.05 to 1000 ng/mL for CEA detection (R² = 0.998), along with an exceptionally low detection limit (LOD) of 0.02383 ng/mL. Moreover, the developed immunosensor demonstrated remarkable selectivity, excellent stability, and satisfactory reproducibility, indicating its significant potential for clinical diagnostic applications.